Student Perceptions Towards Moodle and Kahoot Based e-Learning in Learning Mathematics - Abdullah, Ahmad Anis; Rochmadi, Tri (Proceeding International Conference on Science and Engineering, 2020)
Today’s students are digital natives. They grow with digital technology. Universitas Alma Ata is adapting to learning styles in the digital age by integrating e-learning based learning and classroom learning. The e-learning model that is applied is based on moodle and kahoot. This learning model was introduced to students in September 2017. The meaning of this manuscript is to determine whether the use of moodle and kahoot based e-learning will help students in learning mathematics. It also examines the effect of applying e-learning on student perceptions. Twelve mathematics education students were included in this study. A set of questionnaires was specified to evaluate students’ attitudes and perceptions of learning. From the findings, conclusions have been drawn about the role of moodle and kahoot based e-learning to support the teaching and learning process. The results show that students show positive perceptions using moodle and kahoot based e-learning.